Complex approach to perfection of capillary non-destruction control of aviation engineering elements - Франчук, Г. М.; Овсянкін A. M. (Proceedings of National Aviation University (archive), 2000)
Presented is theoretical substantiation of intensification of cappillar flow detection based on multiphase and multicomponent flows. Considered are methods of calculation of working characteristics of palvarization mechanisms by using gas-dynamic functions